SIMBOL DAN ORNAMEN-SIMBOLIS PADA ARSITEKTUR GEREJA KATOLIK REGINA CAELI DI PERUMAHAN PANTAI INDAH KAPUK-JAKARTA - Reginaldo Christophori Lake (Ide dan Dialog Desain Indonesia (Idealog), 2019)
The Catholic Church building always displays symbols and ornaments as an expression of religious (sacred) faith and atmosphere. Symbols in the form of two-dimensional and three-dimensional objects arranged and beautified the church as well as religious significance. Symbols and ornaments are placed inside the church (interior) and outside the church (exterior), function to support the atmosphere of the church visually and help appreciate aesthetic, psychological and religious faith. Regina Caeli Catholic Church in Pantai Indah Kapuk Jakarta is a Catholic church that is characterized by modern architecture and features symbols and ornaments on the interior and exterior of the church. This paper describes the existence of symbols and ornaments -symbols in the church associated with obedience to the principles of modern architecture that underlies the design of the church. The research problem is how the existence of symbolic symbols and ornaments in the Regina Caeli Catholic Church, which are modern-minimalist architecture? The study was carried out by analyzing secondary data (photos and texts) and literature studies, then compared with the basic guidelines of Catholic church architecture and the principles of modern architecture. As a result, Regina Caeli's Catholic Church architecture is a modern architecture with a modern-minimalist expression. The existence of a symbol of the cross marks the existence of a Catholic church visually, the interior ornaments strengthen the uniqueness as a sacred (religious) space. The Regina Caeli Catholic Church has a modern architecture and provides a place for symbolic symbols and ornaments; there is a mixture of modern architecture with church symbolism as a relogious building.